Enhancing wound healing through innovative technologies: microneedle patches and iontophoresis - Jin, Yong Xun; Ngoc Chien, Pham; Thi Nga, Pham; Zhang, Xin Rui; Ngan Giang, Nguyen; Thi Thuy Le, Linh; Trinh, Thuy-Tien Thi; Zhou, Shu Yi; Nam, Sun Young; Heo, Chan Yeong (Frontiers in Bioengineering and Biotechnology, 2024)
Wound healing is a complex process involving multiple stages, including inflammation, proliferation, and remodeling. Effective wound management strategies are essential for accelerating healing and improving outcomes. The CELLADEEP patch, incorporating iontophoresis therapy and microneedle technology, was evaluated for its potential to enhance the wound healing process. This study utilized a full-thickness skin defect model in Sprague-Dawley rats, researchers compared wound healing outcomes between rats treated with the CELLADEEP Patch and those left untreated. Various histological staining techniques were employed to examine and assess the wound healing process, such as H&E, MT and immunofluorescence staining. Furthermore, the anti-inflammatory and proliferative capabilities were further investigated using biochemical assays. Macroscopic and microscopic analyses revealed that the CELLADEEP patch significantly accelerated wound closure, reduced wound width, and increased epidermal thickness and collagen deposition compared to an untreated group. The CELLADEEP patch decreased nitric oxide and reactive oxygen species levels, as well as pro-inflammatory cytokines IL-6 and TNF-α, indicating effective modulation of the inflammatory response. Immunofluorescence staining showed reduced markers of macrophage activity (CD68, F4/80, MCP-1) in the patch group, suggesting a controlled inflammation process. Increased levels of vimentin, α-SMA, VEGF, collagen I, and TGF-β1 were observed, indicating enhanced fibroblast activity, angiogenesis, and extracellular matrix production. The CELLADEEP patch demonstrated potential in promoting effective wound healing by accelerating wound closure, modulating the inflammatory response, and enhancing tissue proliferation and remodeling. The CELLADEEP patch offers a promising non-invasive treatment option for improving wound healing outcomes.